A comparative study of legislation in the views of âSheikh Fazlollah Nouriâ and âMirza Mohammad Hussein Nainiâ - Ã˜Â§Ã˜Â¨Ã™ÂˆÃ˜Â§Ã™Â„Ã™Â‚Ã˜Â§Ã˜Â³Ã™Â…Ã›ÂŒ Ã˜Â¯Ã™Â‡Ã˜Â§Ã™Â‚Ã˜Â§Ã™Â†Ã›ÂŒ, Ã™Â†Ã˜Â±Ã˜Â¬Ã˜Â³; Ã™ÂˆÃ˜Â±Ã˜Â¹Ã›ÂŒ, Ã˜Â³Ã›ÂŒÃ˜Â¯Ã˜Â¬Ã™ÂˆÃ˜Â§Ã˜Â¯ (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Legislation was one of the concepts and issues of intense debate among different political and religious currents in the Persian Constitutional Era In accordance with the definitions each of these streams of thought provided for legislation and its scope in Islam, various positions were held against the Constitutional Movement having law and legislation as part of its main principles. In this article, the views of Sheikh Fazlollah Nouri and Mirza Mohammad Hussein Naini as representatives of two important currents that were at odds with each other are discussed. And in response to the question of permissibility and non-permissibility of legislation and its territory in the views of these two scholars of the Constitutional Era, a number of issues are mentioned as the reasons for the variety of opinions. These issues include difference of opinions in the range of human legislation, being minimum or maximum (the conventional and the non-authoritative), jurisprudential differences in different understandings of religious texts (different understandings of the political system during the Ghaybah or the Occultation), differences in principles and the methodology of using evidences to infer rules, difference in perspectives towards man and religion. As a result, both views acknowledge the possibility of legislation for human society, where this legislation is based on canonical reasons and fulfilled through Ijtihad of âsovereign rulerâ or âthe National Assemblyâ in an identifiable territory and under certain terms and conditions (not being incompatible with Islam or being consistent with Islam).